Transportation Management in Urban Functional Areas - Gross Marta; Dudzińska Małgorzata; Dawidowicz Agnieszka; Wolny-Kucińska Ada (Real Estate Management and Valuation)
Urban and suburban transport within Functional Urban Areas (FUAs) is now considered an integrated system. In these regions, many residents commute from the suburbs to the city daily for work, education, and social purposes. Transport planning must consider these dynamics to ensure consistent and convenient connections between the city and its suburbs. This article stresses the need for a standardized tool to collect data on transport management models in FUAs across 38 OECD-affiliated countries.